Al-Qur'an Tahfidz Assistance Using the Muraja'ah Method - Jailani, Abdul Kodir; Kustati, Martin; Amelia, Rezki; Gusmirawati; Elysa, Ratianarimamy Niriko (Jurnal Al Maesarah, 2025)
This community service aims to evaluate students' ability to enhance the quality of their Qur'an memorization through the implementation of the muraja'ah method at Pondok Tahfidz Ustadz Mahyuddin (PTUM), Padang City. PTUM is an Islamic educational institution that actively contributes to the development of Qur'anic literacy within the community. The muraja'ah method, which involves repeated review of previously memorized verses, is employed to ensure retention and prevent forgetting. The study utilizes the Participatory Action Research (PAR) approach, conducted in three stages. First, during the preparation stage, students are divided into groups based on their reading and memorization proficiency, and the necessary resources for muraja'ah activities are prepared. Second, in the implementation stage, activities begin with a joint prayer, followed by tahsin (improving reading quality), muraja'ah (reviewing memorized verses), and ziyadah (adding new memorization). Third, the evaluation stage involves regular assessments recorded on individual memorization papers to monitor progress. The results demonstrate that the muraja'ah method effectively improves students' memorization quality. This is reflected in the increased accuracy, fluency, and retention of their memorization. Based on the mentoring activities conducted, it can be concluded that the muraja'ah method serves as an effective approach to enhance and sustain the quality of Qur'an memorization.